Assessment of isometric strength of the shoulder rotators in swimmers using a handheld dynamometer: a reliability study - Conceiçao, A.; Parraca, J.; Marinho, D.; Costa, M.; Louro, H.; Silva, A.; Batalha, N. (Acta of Bioengineering and Biomechanics, 2018)
Purpose: The purpose of this study was to determine the reliability of shoulder isometric strength assessment using the microfet 2™ dynamometer in adolescent swimmers. Methods: Twenty-nine participants (16.2 ± 1.2 years old; 59.05 ± 6.98 kg of body mass) were tested using the microfet 2™ dynamometer. Swimmers performed an isometric strength test (IST) in two distinct occasions with 7 days apart in order to calculate the reliability. All participants were asked to perform a maximal isometric contraction from the external and internal shoulder rotators in a prone body position. Results: The external and internal shoulder rotators showed an excellent intraclass correlation coefficients for both shoulders, with more than 0.90 and a low percentage of method error variation. The external/internal ratios reliability was good in dominant (ICC 0.80) and non-dominant (ICC 0.81) shoulders. The reliability using Bland-Altman method showed that systematic errors (mean difference between test-retest) were nearly zero and the 95% limits of agreement narrow, indicating a good reliability. Conclusions: It can be concluded that microfet 2™ is a reliable apparatus for measuring the strength of the external and internal rotation of the shoulder in swimmers. Its light weight and easy portable characteristics can help swimming coaches monitoring specific dry-land strength training programs for their swimmers.